DWT 2020
DOI: 10.5004/dwt.2020.26339
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of printing and packaging wastewater by electrocoagulation-flotation: the simultaneous efficacy of critical parameters and economics

Abstract: In this work, electrocoagulation-flotation (ECF) following sedimentation was applied as a printing and packaging wastewater treatment using four Al electrodes with a parallel monopolar configuration. A sedimentation process was applied after the ECF as a post-treatment phase to remove large pollutants. The simultaneous efficacy of the operating parameters initial color content (1,843.44-12,156.56 ADMI), initial pH (3.56-10.44), current density (6.02-22.18 mA/cm 2), and treatment time (5.62-74.38 min) on color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…(Alobaidy et al 2010). Drinking water in Iraq is secured from rivers, lakes, wells and springs, which are usually exposed to various pollutants that result from the diffusion from non-point and point sources (Hashim et al 2021a;Omran et al 2021), which are difficult to control, monitor, and evaluate, such as sewage (Hashim et al 2020a;Zanki et al 2020), agricultural and industrial effluents (Emamjomeh et al 2020a(Emamjomeh et al , 2020b. In addition, global warming plays a serious role in the freshwater shortage in Iraq (Zubaidi et al 2020a;Zubaidi Salah et al 2020), where the last studies revealed a significant shortage in precipitations (Salah et al 2020b(Salah et al , 2020c.…”
Section: Introductionmentioning
confidence: 99%
“…(Alobaidy et al 2010). Drinking water in Iraq is secured from rivers, lakes, wells and springs, which are usually exposed to various pollutants that result from the diffusion from non-point and point sources (Hashim et al 2021a;Omran et al 2021), which are difficult to control, monitor, and evaluate, such as sewage (Hashim et al 2020a;Zanki et al 2020), agricultural and industrial effluents (Emamjomeh et al 2020a(Emamjomeh et al , 2020b. In addition, global warming plays a serious role in the freshwater shortage in Iraq (Zubaidi et al 2020a;Zubaidi Salah et al 2020), where the last studies revealed a significant shortage in precipitations (Salah et al 2020b(Salah et al , 2020c.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradation, solvent extraction, ion exchange, oxidation, and adsorption are some of the processes involved (Sivarajasekar & Baskar 2015;Sharma & Kaur 2018;Hashim et al 2021b). For example, the electrocoagulation method is currently in use for dye removal from solutions (Emamjomeh et al 2020;Abdulhadi et al 2021;Hashim et al 2021a). Hashim et al (2019) used an electrocoagulation cell to remove black reactive dyes from water under different experimental conditions and found the removal efficiency reached 96%.…”
Section: Introductionmentioning
confidence: 99%
“…The theme of sustainability has gained considerable attention in recent years via environmental organizations and departments worldwide, particularly with regard to the issues of addressing the pollution of the basic elements of the environment (water, air, soil) and the sustainability required for treatment techniques (Furley et al 2018). For instance, water bodies are facing severe deterioration due to the discharge of wastewaters, which results in a remarkable increase in heavy metals (Abdulla et al 2020;Abdulraheem et al 2020), coloring agents (Abdulhadi et al 2019;Aqeel et al 2020), nutrients (Alenezi et al 2020;Al-Marri et al 2020;Khalid et al 2020aKhalid et al , 2020b, phenols (Emamjomeh et al 2020a(Emamjomeh et al , 2020b, geosmin (Ryecroft et al 2019), fluoride (Alhendal et al 2020), organic pollutants (Abdulhadi et al 2021;Alyafei et al 2020;Zanki et al 2020), viruses and bacteria (Hashim et al 2020a(Hashim et al , 2020bHashim et al 2021;Khalid et al 2020aKhalid et al , 2020b, turbidity (Alenazi et al 2020;Alnaimi et al 2020) and other pollutants (Emamjomeh et al 2020a(Emamjomeh et al , 2020bHashim et al 2020aHashim et al , 2020bKadhim et al 2020b;Mohammed et al 2020). Air quality is also deteriorating due to the increasing emissions from human activities (Grmasha et al 2020;Kadhim et al 2020a;Shubbar et al 2020aShubbar et al , 2020b, such as cement industries (Majdi et al 2020;…”
Section: Introductionmentioning
confidence: 99%